HEREDITARY MULTIPLE PRIMARY BREAST AND OVARIAN CANCER (CASE REPORT) - Е. V. Panferova; L. F. Pisareva; I. N. Odintsova; L. V. Khyshiktuev; D. М. Ponomarenko; N. V. Cherdyntseva (Сибирский онкологический журнал)
A case report on BRCA1-associated hereditary multiple primary breast and ovarian cancer has been presented. Platinum-containing chemotherapy resulted in favorable treatment outcomes.